Youth Empowerment by the Karang Taruna Organization in Kertasari Subdistrict, Ciamis Regency - Raihan Khairi Firdaus; Regi Refian Garis; Neti Sunarti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research was motivated by the suboptimal youth empowerment efforts of the Karang Taruna organization in Kertasari Village, Ciamis District, Ciamis Regency. During fieldwork, the researcher identified a lack of organized activities by the Karang Taruna and low youth participation in Kertasari Village. This study used a qualitative descriptive method. Data was collected through observation, interviews, and documentation. Data processing and analysis involved three steps: data reduction, data presentation, and conclusion drawing. A total of six informants were included in the study. The research aimed to determine the level of youth participation in the Karang Taruna organization in Kertasari Village, Ciamis District, Ciamis Regency. Based on the findings, the youth empowerment efforts of the Karang Taruna organization have shown some progress but are not yet optimal when measured against the stages of empowerment theory by Ambar T. (2017). This is supported by indicators like a growing sense of awareness, increased community consciousness, and creativity all of which show development. However, several obstacles were identified, including low interest and participation from youth, as well as limited facilities and resources like training equipment and funding. The Karang Taruna's efforts to overcome these challenges include personal outreach to youth, using social media to share information and improve communication, and adjusting activity schedules to be more flexible and not conflict with young people's daily routines.